New Technology of Thermoplastic Coating for Osmotic Pump Tablets: Study on in vivo Drug Release - Chun Ping Yuan; Hui Min Hou; Zhi Hong Cheng; Qing Hua Ge; Ding Zhong Song; Jian Qiang Xi (Georg Thieme Verlag KG, 2020)
Aim The in vivo pharmacokinetics of thermoplastic-coated tablets prepared by a new technology of thermoplastic coating in Beagle dogs were studied, and the correlation between in vitro release and in vivo absorption was analyzed. Methods The in vitro release profiles of metformin hydrochloride thermoplastic-coated tablets and nifedipine thermoplastic-coated tablets were investigated. The single-dose pharmacokinetic study of these tablets in Beagle dogs was performed, and the obtained results were separately compared with the data of conventional osmotic pump tablets reported in the literature. Results Metformin hydrochloride thermoplastic-coated tablets and nifedipine thermoplastic-coated tablets displayed controlled drug-release characteristics and had a good in vivo-in vitro correlation in Beagle dogs, respectively. The literature-compared results further demonstrated that both thermoplastic-coated tablets had release characteristics of osmotic pump tablets in vivo. Conclusion The thermoplastic-coated tablets could control drug release in vivo and it was further confirmed that the new thermoplastic coating technology could replace the spray coating of osmotic pump controlled-release tablets. This study provides a theoretical basis and practical support for the industrialization and clinical application of the new thermoplastic coating technology.